2019
DOI: 10.1016/j.tim.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Bipartite Metabolism of Intracellular Pathogens

Abstract: The host is a nutrient-rich niche for microbial pathogens, but one that comes with obstacles and challenges. Many intracellular pathogens like Legionella pneumophila, Coxiella burnetii, Listeria monocytogenes, and Chlamydia trachomatis have developed bipartite metabolism within their hosts. This style of metabolic regulation enables pathogen sensing of specific nutrients to engage them into catabolic and anabolic processes, and contributes to temporal and spatial pathogen phenotypic modulation. Not only have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 104 publications
1
34
0
Order By: Relevance
“…In general, there is no clear consensus in literature regarding if T. cruzi infection causes a reduction or an increase in the expression of genes controlling the energy production of the cell. Previous studies showed similar downregulation of oxidative phosphorylation genes in cardiomyocytes infected by distinct T. cruzi strains (Garg et al, 2003;Vyatkina et al, 2004;Manque et al, 2011;Best and Abu Kwaik, 2019). Experiments in vivo using mouse models during early timepoints, are in consistency with our findings that these genes decrease expression over disease progression (Garg et al, 2003;Vyatkina et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, there is no clear consensus in literature regarding if T. cruzi infection causes a reduction or an increase in the expression of genes controlling the energy production of the cell. Previous studies showed similar downregulation of oxidative phosphorylation genes in cardiomyocytes infected by distinct T. cruzi strains (Garg et al, 2003;Vyatkina et al, 2004;Manque et al, 2011;Best and Abu Kwaik, 2019). Experiments in vivo using mouse models during early timepoints, are in consistency with our findings that these genes decrease expression over disease progression (Garg et al, 2003;Vyatkina et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, the inhibition of MAP kinases and the NFκB pathway are mechanisms that pathogenic bacteria can exploit to increase their chances of survival inside a host cell (Cornejo et al, 2017). Additionally, pathogenic bacteria have mechanisms for inhibiting host protein translation to increase the availability of amino acids in the cytosol and can act to augment the uptake of nutrients from the cell (Best and Abu Kwaik, 2019). The data obtained in this study indicates that an unique capability to inhibit translation is also present in some strains of T. cruzi and may be an important mechanism to allow the persistence of the parasite in a specific organ.…”
Section: Discussionmentioning
confidence: 99%
“…This work illustrates that bacteria adapt their Q salvage strategies to their environments. Bacteria that are located inside a human cell such as C. trachomatis have streamlined their metabolism and rely on import for many nutrients (57)(58)(59)(60). Only q or Q are supposedly available in the intracellular environment, and we show here that Chlamydiae species have evolved to salvage the q base: a YhhQ family member (CT140) imports q, and a bacterial TGT homolog (CT193) catalyzes the base exchange between q and the target guanine in tRNAs.…”
Section: Discussionmentioning
confidence: 83%
“…An emerging concept in bacterial pathogenesis is nutritional virulence, whereby intracellular bacteria are specifically adapted to obtain essential nutrients by exploiting host metabolic processes (37). Several bacteria, including Anaplasma phagocytophilum and Francisella tularensis, utilize host autophagy for nutrient acquisition (6). Investigators have speculated that C. burnetii can also obtain nutrients from the host via CCV fusion with autophagosomes (6, 9).…”
Section: Discussionmentioning
confidence: 99%
“…transporting nutrients through a vacuole membrane barrier. Legionella pneumophila is phylogenetically related to C. burnetii and exploits the host's neutral amino acid transporter, solute carrier (SLC) 1A5, to obtain amino acids from the cytoplasm (6)(7)(8). Unlike other vacuolar bacteria, C. burnetii resides within a harsh phagolysosome-like compartment that is thought to be a rich source of nutrients delivered by fusion with endocytic and autophagic vesicles (9,10).…”
mentioning
confidence: 99%